2019
DOI: 10.1136/bmj.l5584
|View full text |Cite
|
Sign up to set email alerts
|

Weight change across adulthood in relation to all cause and cause specific mortality: prospective cohort study

Abstract: ObjectiveTo investigate the association between weight changes across adulthood and mortality.DesignProspective cohort study.SettingUS National Health and Nutrition Examination Survey (NHANES) 1988-94 and 1999-2014.Participants36 051 people aged 40 years or over with measured body weight and height at baseline and recalled weight at young adulthood (25 years old) and middle adulthood (10 years before baseline).Main outcome measuresAll cause and cause specific mortality from baseline until 31 December 2015.Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
182
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(222 citation statements)
references
References 41 publications
19
182
0
1
Order By: Relevance
“…Obesity is a major risk factor for various chronic diseases. To make matters worse, excessive weight gain from young to middle adulthood was associated with increased risks of all-cause mortality [30] . Indeed, adiposity has long term harmful consequences, which predicts sharp growth of chronic disease burden and premature death in the future in China.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is a major risk factor for various chronic diseases. To make matters worse, excessive weight gain from young to middle adulthood was associated with increased risks of all-cause mortality [30] . Indeed, adiposity has long term harmful consequences, which predicts sharp growth of chronic disease burden and premature death in the future in China.…”
Section: Discussionmentioning
confidence: 99%
“…The study design is shown in Figure S1. The NHANES study design has been described in detail previously [12,15].…”
Section: Study Design and Populationmentioning
confidence: 99%
“…Due to the relatively limited number of deaths occurring in early adulthood, we were not able to examine the effect of obesity treatment response on risk of mortality. However, it is well-established that weight loss has positive long-term health benefits [4,17,46], and has in adults been shown to reduce the risk of premature mortality [25]. Future research should investigate whether successful obesity treatment can lead to a reduction in the risk of early mortality.…”
Section: Children and Adolescents With Obesity And Premature Deathmentioning
confidence: 99%
“…While 1 study found a correlation between adolescent BMI and mortality risk before the age of 30 years [19], 2 of the studies did not find such an association [20,22]. High BMI in young adulthood has been associated with a higher risk of premature death later in life, largely driven by cardiovascular disease and other noncancer diseases [23][24][25]. To our knowledge, there are no current studies on risk of mortality in young adulthood in relation to measured height and weight in childhood.…”
Section: Introductionmentioning
confidence: 96%